Air Pollution and Its Impact on Global Environment - Sukla, Dr. Om Prakash (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
A pollutant is a substance that may be defined as constituents in the wrong amount at the wrong place or at the wrong time .Pollution may be of various types depending upon the medium which are adversely affected by the pollutants. These are water pollution, air pollution, agricultural pollution, radiation pollution thermal pollution and, noise pollution. Air pollution may be categorized in to indoor and outdoor pollution. Pollution of atmosphere inside buildings, offices and residence is called indoor air pollution and the atmospheric pollution in the open space is referred to as outdoor air pollution. The UN agency had recently also linked air pollution with increasing child mortality. India (2017) witnessed 1.10 lacs premature death of children due to air pollution ,highest in the world in the category of children under five years of age .. According Randeep Guleria Director of AIIMS upsurge in respiratory problem in the winter month with peak air pollution is well known particularly in north India Keyword: Pollution, atmosphere, environment, factories